Adolescence and beyond family processes and development - Kerig, Patricia; Schulz, Marc S.; Hauser, Stuart T. (Oxford : Oxford University Press, 2012)
The period of transition from adolescence to adulthood has become a recent focus for developmental psychologists and child mental health practitioners, but the full role of the family during this period is only beginning to be explored. Many compelling questions, of interest to anyone involved in adolescence research, remain unanswered.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Adolescence; Adolescent psychology; Teenagers -- Family relationships; Teenagers -- Sexual behavior